2016
DOI: 10.1007/s00253-016-7687-1
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of acetoin production in metabolically engineered Lactococcus lactis by increasing ATP demand

Abstract: Having a sufficient supply of energy, usually in the form of ATP, is essential for all living organisms. In this study, however, we demonstrate that it can be beneficial to reduce ATP availability when the objective is microbial production. By introducing the ATP hydrolyzing F-ATPase into a Lactococcus lactis strain engineered into producing acetoin, we show that production titer and yield both can be increased. At high F-ATPase expression level, the acetoin production yield could be increased by 10 %; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 32 publications
3
49
0
Order By: Relevance
“…Consequently, cells have to be forced to high glucose uptake rates even when they are not growing. As the ATP maintenance demand seems to be the main driving force for itaconic acid production in this phase, ATP‐wasting strategies (Hädicke, Bettenbrock, & Klamt, 2015; Hädicke and Klamt, 2015; Liu, Kandasamy, Wurtz, Jensen, & Solem, 2016) could be used to increase substrate turnover. Besides, manipulation of regulatory networks (Michalowski, Siemann‐Herzberg, & Takors, 2017) and certain nutrient limitations (Chubukov & Sauer, 2014) might further increase uptake rates.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, cells have to be forced to high glucose uptake rates even when they are not growing. As the ATP maintenance demand seems to be the main driving force for itaconic acid production in this phase, ATP‐wasting strategies (Hädicke, Bettenbrock, & Klamt, 2015; Hädicke and Klamt, 2015; Liu, Kandasamy, Wurtz, Jensen, & Solem, 2016) could be used to increase substrate turnover. Besides, manipulation of regulatory networks (Michalowski, Siemann‐Herzberg, & Takors, 2017) and certain nutrient limitations (Chubukov & Sauer, 2014) might further increase uptake rates.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that, in cells where biomass and ATP synthesis are coupled with product synthesis, enforced ATP wasting due to futile cycles or other mechanisms dissipating ATP may (1) boost the specific substrate uptake and product synthesis rate and (2) increase the product yield . These results were obtained for OSF processes but they may have a favorable effect also for TSF processes, especially due to the potential to boost substrate consumption in the production phase.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism must be robust enough to ensure that the amount of ATP wasted is not too high as it would drive the cell into an unstable state. Regarding OSF processes, enforced ATP wasting strategies have a beneficial effect on product yield as well as on specific substrate uptake and production rates (see simulations in Figure and experimental proofs in Refs ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulating the adenosine triphosphate (ATP) pool has been a major target for enhancing the performance of production organisms . For pathways with ATP limitations, increasing the pool of available ATP may improve the production of desired compounds, e.g., of succinic acid or of recombinant proteins .…”
Section: Introductionmentioning
confidence: 99%